PENGARUH RELATIONSHIP MARKETING DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA PT. MEX BARLIAN DIRGANTARA PEKANBARU - Aisyah, Ade; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted in Mex Barlian Dirgantara Pekanbaru, located on Meranti Street, Labuh Baru Timur Village, Payung Sekaki District. The purpose of this study was to determine the effect of relationship marketing and service quality on customer loyalty in the use of goods delivery services at PT. Mex Barlian Dirgantara Pekanbaru. Relationship marketing and service quality (X1-X2) meanwhile customer loyalty (Y). The research method used is quantitative descriptive analysis obtained from the results of a questionnaire measured by a Likert scale which is then processed with SPSS version 16. The sample of this study was 100 respondents from the population calculated using the Slovin formula. This research uses simple linear regression analysis method and multiple linear regression analysis. The results of the analysis show that relationship marketing and service quality have an effect on increasing consumer loyalty, either partially or simultaneously. The results of the analysis show that the coefficient of determination is 0.429, meaning that 42.9% change in the value of customer loyalty is influenced by relationship marketing and service quality variables while the remaining 57.1% is influenced by other variables not examined in this study. Keywords: Relationship Marketing, Service Quality, Customer Loyalty